RENEWABLE ENERGY IMPACT ON SUSTAINABLE DEVELOPMENT IN INDIA: OPPORTUNITIES & CHALLENGES - Pachar, Sunita; Garg, Shaifali (International Journal of Psychosocial Rehabilitation, 2020)
For every developing country energy is a very important source for economic & industrial development. India is a growing economy and it would need an assured supply of 3–4 times than the whole energy consumed today. Environment issues which are related with coal, oil and crude oil as non –renewable energy can be resolved by renewable energy (RE) sources like wind, solar and thermal which are sustainable and have a huge potential to satisfy Indian energy consumption need. This research paper discussed about renewable energy sources, drivers, challenges and policies. It can be concluded from review of literature and other information provided in paper that Renewable energy have a huge potential in India and with effective technologies use it can fulfill India’s energy demand in future. Quality of life can be improved with the help of energy. The paper also focused on Government regulations and institutions which are contributing in renewable energy up-gradation. It is predictable that large number of domestic jobs can be created in future in green energy and RE. This paper shows achievements and future potential of India in energy sector. The study found that renewable energy can reduce environment pollution issues, carbon emission and scarcity of nonrenewable energy sources .RE has a positive relation with economic growth, job creation and welfare.